Guidelines and management of mild hypertensive conditions in pregnancy in rural general practices in Scotland: issues of appropriateness and access. Issue 4 (1st August 2003) - Tucker, J; Farmer, J; Stimpson, P
Abstract : Objectives: To assess the diagnosis and management of mild non-proteinuric hypertension in pregnancy in rural general practices against guideline recommendations. Design: Postal survey and telephone interview. Setting: All 174 designated rural general practices in Scotland. Sample: 171 GPs and 158 midwives responsible for antenatal care stratified by distance from a specialist maternity hospital. Main outcome measures: Accuracy of diagnosis and appropriateness of management compared with guideline. Results: At least one respondent replied for 91% (158/174) of rural practices. Response rates were 68% (117/170) for GPs and 77% (121/158) for midwives. Both GP and midwife replied for 46% (80/174) of practices. Most GPs (80%, 87/109) and midwives (63%, 71/113) overdiagnosed the scenario. Intended management was therefore most often referral or admission to specialist hospital (59%, 132/224), both courses of action beyond guideline recommendations. There was an association between distance of practice from specialist maternity hospital and professionals' report of intended referral or admission. Explanatory factors from telephone interviews included a poor knowledge base, cautious risk assessment, and perceived inflexibility of guidelines for remote situations. Conclusions: There is a lack of accuracy in the diagnosis of a common antenatal problem and intended management is consistent with overdiagnosis. The results suggest that women in rural settings may experience more antenatal referrals and admissions than are clinically appropriate according to the guidelines. At a time of increasing centralisation of maternity services, this could increase inappropriate referrals and increase costs to service and patients. Quality of care may be improved by developing consensual local guidelines with rural maternity care professionals and support maintained skills and confidence in decision making.